UPAYA VIETNAM DALAM MENINGKATKAN PEREKONOMIANNYA MELALUI SEKTOR PERDAGANGAN INTERNASIONAL TAHUN 2001-2006 - Honesty, Christine Wita (Global and Policy Journal of International Relations, 2015)
ABSTRACTThis study discusses the Vietnamese government's efforts in improving its economy through international trade sectors in 2001-2006. The background of this study was the change in government policy on the Vietnam that previously focused on state ideology, be a policy that focuses on economic growth called Doi Moi policy. Since Doi Moi imposed, the Vietnamese government has become more open in terms of cooperative relationships with other countries but especially in the sector of international trade. It later became the main platform issues examined in this study, namely how Vietnamese government's efforts in improving its economy through international trade sector. Those problems were analyzed using descriptive methods by making the theory of Economic Growth and Structural Change as a basis for argument. From the theoretical approach is given, while the response that Vietnam's efforts in improving its economy through international trade sectors in the years 2001-2006 implemented through the international economic cooperation.Key Words : Doi Moi, Economic Growth, Structural Change, BTA, WTODOI:https://doi.org/10.33005/jgp.v3i01.1960